2023
DOI: 10.13189/saj.2023.110214
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Dietary Supplements among Arab Olympic Athletes and Coaches in Preparation Program for Tokyo 2020 Olympic Games

Abstract: Nutrition plays an important role as a key factor in the performance of athletes and their coaches, so good and proper nutrition is essential for improving athletic performance and physical fitness. The lack of nutritional knowledge of athletes may affect their performance, and the most important of these issues is nutritional knowledge of food and dietary supplements Aim: To assess the nutritional knowledge, attitude, and practice of athletes and their coaches at the Arab Olympic Preparation Center about the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Dietary supplements play a crucial role in building muscle, boosting the immune system, and providing fuel to enhance training or athletic performance. Elite athletes often utilize performance-enhancing agents, with many considering supplements to be an essential component for sports success ( 118 ). A Canadian study revealed that 87% of elite male and female athletes used supplements regularly ( 112 ), while another study conducted in Canada found that 98% of young athletes between the ages of 11 and 25 used supplements on a regular or intermittent basis ( 119 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dietary supplements play a crucial role in building muscle, boosting the immune system, and providing fuel to enhance training or athletic performance. Elite athletes often utilize performance-enhancing agents, with many considering supplements to be an essential component for sports success ( 118 ). A Canadian study revealed that 87% of elite male and female athletes used supplements regularly ( 112 ), while another study conducted in Canada found that 98% of young athletes between the ages of 11 and 25 used supplements on a regular or intermittent basis ( 119 ).…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient understanding of nutrition among athletes has the potential to impact their performance ( 1 , 2 ). It is crucial for adolescent athletes to embrace a healthy eating regimen to adequately fulfill their nutritional requirements, foster well-being, and optimize their athletic performance ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%